2007
DOI: 10.1007/s12011-007-8016-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Dunaliella tertiolecta to Lead and Aluminum: Toxicity and Effects on Ultrastructure

Abstract: The growth response of the marine alga Dunaliella tertiolecta to different concentrations of lead and aluminum was investigated. Both metals had a stimulatory effect at low concentration and an inhibitory effect at high concentration (hormesis). The IC25 values of lead are 8.43, 7.29, and 6.74 mg L-1 for 24, 48, and 72 h, respectively. The corresponding values for aluminum are 30.54, 22.42, and 18.16 mg L-1. Although it seems that the two metals are not directly toxic to the alga at the concentrations found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…Like in other algae (Nassiri et al. 1997a,b, Sacan et al. 2007), Al‐ and Cu‐treated Micrasterias cells featured an increased number of vacuoles with electron‐dense precipitations.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Like in other algae (Nassiri et al. 1997a,b, Sacan et al. 2007), Al‐ and Cu‐treated Micrasterias cells featured an increased number of vacuoles with electron‐dense precipitations.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the uncommonly thick primary wall and its bloated appearance induced in young semicells by Al and also by Cu may be a result of a loss of the Ca 2+ bonds of pectins. Al‐treated cells also showed a wavy plasma membrane, which was also observed in Dunaliella tertiolecta after Al exposure (Sacan et al. 2007).…”
Section: Discussionmentioning
confidence: 74%
“…Cordero et al [41] reported a Pb 2+ DE 50 (dose that inhibits in 50% the growth of the species) of 0.4 mg L −1 for the microalgae Tetraselmis chuii. Pb 2+ concentrations over 0.5 mg L −1 affected the Dunaliella tertiolecta cell ultrastructure, leading to the rupture of the tilacoid membrane, the build-up of polyphosphate bodies, and the precipitation of Pb 2+ on the cell wall [42]. However, this species resists high concentrations of Pb 2+ , presenting a DE 25 (dose that inhibits in 25% the growth of the species) of 8.43 mg L −1 after 24 h.…”
Section: Inhibition Of M Novacekii Cell Growth By Pb 2+mentioning
confidence: 99%
“…Aluminum (Al) plays an important role in marine ecosystems due to its inhibition or promotion effects on phytoplankton (Vrieling et al 1999, Saçan et al 2007, although its concentration is very low as it is a particle-reactive element, easily removed from seawater (Minakawa & Watanabe 1998, Koshikawa et al 2002. Naturally, marine dissolved Al is mainly derived from atmospheric precipitations and river run-offs, and its concentration is thus increasing as a result of increasing severe sandstorms and acidic precipitations caused by atmospheric pollution (Han et al 2008, Ren et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Al on marine organisms were also observed to be species-specific, e.g. Vrieling et al (1999) found that the increased Al positively affected the growth and final cell density of pennate Navicula salinarum, but not of centric species Thalassiosira weissflogii; while Saçan (2007) found that Al negatively affected the growth of diatom Minutocellus polymorphus and green alga Dunaliella tertiolecta. However, a limited Al effect was observed for the growth of diatom Skeletonema costatum (Stoffyn 1979); and no significant effects were detected on the brown macroalga Hormosira banksii, sea urchin embryo Heliocidaris tuberculata and 2 juvenile fish species of Lates calcarifer and Acanthochromis polyacanthus, even at an extremely high Al level (37 μmol l -1 ) (Golding 2014).…”
Section: Introductionmentioning
confidence: 99%